The wren in the Holly Library - Linde, K. A. (Red Tower Books, 2024)
Trapped in the library of an old Brownstone with a monster filled with terrible power and darkness, street thief Kierse, when, instead of killing her, the monster offers her a job--gets a glimpse into who she really is, which could be something far worse than a monster.